Effect of promoter and noble metals and suspension pH on catalytic nitrate reduction by bimetallic nanoscale Fe0 catalysts. Issue 9 (2nd May 2016) - Bae, Sungjun; Hamid, Shanawar; Jung, Junyoung; Sihn, Youngho; Lee, Woojin
ABSTRACT: Experiments were conducted to investigate the effect of experimental factors (types of promotor and noble metals, H2 injection, and suspension pH) on catalytic nitrate reduction by bimetallic catalysts supported by nanoscale zero-valent iron (NZVI). NZVI without H2 injection showed 71% of nitrate reduction in 1 h. Cu/NZVI showed the almost complete nitrate reduction (96%) in 1 h, while 67% of nitrate was reduced by Ni/NZVI. The presence of noble metals (Pd and Pt) on Cu/NZVI without H2 injection resulted in the decrease of removal efficiency to 89% and 84%, respectively, due probably to the electron loss of NZVI for formation of metallic Pd and Pt. H2 injection into Cu-Pd/NZVI suspension significantly improved both catalytic nitrate reduction (>97% in 30 min) and N2 selectivity (18%), indicating that adsorbed H on active Pd sites played an important role for the enhanced nitrate reduction and N2 selectivity. The rapid passivation of NZVI surface resulted in a dramatic decrease in nitrate reduction (79–28%) with an increase in N2 selectivity (8–66%) as the suspension pH increased from 8 to 10.